Advances in Human Dendritic Cell-Based Immunotherapy Against Gastrointestinal Cancer - Ni, Ling (Frontiers in Immunology, 2022)
Dendritic cells (DCs), the strongest antigen-present cells, have become a focus for engaging the immune system in the fight against cancer. Basic scientific investigations elucidating cellular biology of the DCs have resulted in new strategies in this fight, including cancer vaccinology, combination therapy and adoptive cellular therapy. Although immunotherapy is now enjoying unprecedented bench-to-bedside clinical success, the overall response rate to the current immunotherapy in patients with gastrointestinal (GI) cancers is pretty low. In this review paper, we have conducted an extensive literature search of the studies of DCs in the treatment of GI patients. We provide the advances in DC-based immunotherapy and highlight clinical trials that demonstrate therapeutic efficacy and toxicities associated with each vaccine. Moreover, we also offer the yet to be elucidated questions and future promise within DC-based immunotherapy. This study focuses predominantly on data derived from human studies to help understand the involvement of DCs in patients with GI cancers.